Light exclusion influence on grape anthocyanin - Jungmin Lee (Heliyon, 2017)
This study contrasted the anthocyanins of investigational grape clusters that developed without light incidence (light-excluded), to those of control clusters that were shaded naturally beneath the vine canopy (control-shaded). Treatment grape clusters were light-excluded during ripening by opaque white polypropylene enclosures; temperature, vapor pressure deficit, and light intensity were measured continually. All 15 ‘Merlot’ grape anthocyanins accrued in both groups, indicating no accumulations were terminated from light-exclusion during ripening. Light-excluded clusters had an overall lower anthocyanin concentration (98.1 mg/100 g of berries) than that of control clusters (162.0 mg/100 g of berries), but it was not significantly different. Light-excluded clusters showed altered concentrations of nine individual anthocyanins that were significantly higher in control-shaded clusters. Although the changes in anthocyanin composition could not be attributed solely to the elimination of light, as there were also deviations in berry temperature and vapor pressure deficit concurrent with preventing light from reaching the treatment clusters.